Mental health conditions and use of rhythm control therapies in patients with atrial fibrillation: a nationwide cohort study - Juha Hartikainen; Jukka Putaala; Jari Haukka; Fausto Biancari; Pirjo Mustonen; Miika Linna; Konsta Teppo; Jussi Jaakkola; Olli Halminen; Janne Kinnunen; Mika Lehto; Alex Luojus; et al. (BMJ Open, 2022)
Objectives Mental health conditions (MHCs) have been associated with undertreatment of unrelated medical conditions, but whether patients with MHCs face disparities in receiving rhythm control therapies for atrial fibrillation (AF) is currently unknown. We assessed the hypothesis that MHCs are associated with a lower use of antiarrhythmic therapies (AATs).Design A nationwide retrospective registry-based cohort study.Setting The Finnish AntiCoagulation in Atrial Fibrillation cohort included records on all patients with AF in Finland during 2007–2018 identified from nationwide registries covering all levels of care as well as drug purchases. MHCs of interest were diagnosed depression, bipolar disorder, anxiety disorder, schizophrenia and any MHC.Participants We identified 239 222 patients (mean age 72.6±13.2 years; 49.8% women) with incident AF, in whom the prevalence of any MHC was 19.9%.Outcomes Primary outcome was use of any AAT, including cardioversion, catheter ablation, and fulfilled antiarrhythmic drug (AAD) prescription.Results Lower overall use of any AAT emerged in patients with any MHC than in those without MHC (16.9% vs 22.9%, p<0.001). Any MHC, depression, bipolar disorder, anxiety disorder and schizophrenia were all associated with lower incidence of any AAT with adjusted subdistribution HRs of 0.790 (95% CI 0.771 to 0.809), 0.817 (0.796 to 0.838), 0.811 (0.789 to 0.835), 0.807 (0.785 to 0.830) and 0.795 (0.773 to 0.818), respectively. Adjusted rates of AAD, cardioversion and catheter ablation use were lower in all MHC groups compared with patients without MHC. The findings in patients with any MHC were confirmed in propensity score matching analysis.Conclusions Among patients with AF, a clear disparity exists in AAT use between those with and without MHCs.Trial registration number ClinicalTrials Identifier: NCT04645537; ENCePP Identifier: EUPAS29845.